A model of a small open economy integrated in a monetary union - Adão, Bernardino (2018)
This paper develops a model of a small open economy integrated in a monetary union, which is a nontrivial technical extension of the existing small open economy model. The model is used to study the monetary transmission mechanism in Portugal.